Elevated ferroptosis is associated with elevated T cells in patients with heat stroke - Qi Cui; Zhongyan Xu; Daxin Lei; Chao Yu; Yuling Luo; Jie Zheng; Fukun Wang (Molecular Biology Reports, 2026)

Ferroptosis-like cell death associated with Vibrio parahaemolyticus infection in the clam Meretrix petechialis - Shujing Zhang; Fengxia Xu; Mengyao Gao; Yu Cui; Yuling Dong; Shuang Jiao; Changjian Xie; Iseult Lynch; Zhiling Guo; Qiuxiang Pang (Fish & Shellfish Immunology, 2026)

Metabolic reprogramming for post-acidification control in fermented milk via post-sterilization treatment - Han Lu; Liru Cui; Menglu Li; Yuling Xue; Yannan He; Chang Liu; Yan Wu; Shijie Wang (Food Microbiology, 2026)

Incorporating dynamic ozone stress and parameter optimization into the BEPS model for improved GPP simulation - Jian Wang; Yuling Du; Jibo Yue; Tianxiang Cui; Yumin Chen; Lin Sun; Lei Shi (Ecological Modelling, 2026)

Environmental Gating of Cerium Species- versus Contact-Associated Toxicity in Rod-Like Cerium Nanomaterials - Yiqing Chen; Jiahui Zhao; Yuling Dong; Kang Zheng; Changjian Xie; Di Cui (Aquatic Toxicology, 2026)

Co-infection with CAV facilitates ALV-K replication and induces severe immunosuppression in chickens - Yuling Cui; Mengyue Dong; Zhanxin Wang; Yang Liu; Jiajia Liu; Hainuo Zeng; Runlin Shao; Ruiheng Liu; Yuanjia Liu; Qingmei Xie; Xinheng Zhang (Veterinary Microbiology, 2026)

Cationic Dendrimer-Directed Pore Architecture in Polyamide Membranes for Tunable Ion Separation - Bingbing Yuan; Menghan Wu; Jinmiao Cui; Lei Zhang; Zequn Liao; Ping Hu; Yuling Ren; Lihong Liu; Siheng Zhao; Meng You; Dongxiao Yang; Q. Jason Niu (Water Research, 2026)

Corrigendum to ‘Exploring nonlinear responses of hydrodynamics and algal biomass to restoration measures in a eutrophic shallow urban lake’ [Journal of Contaminant Hydrology 281 (2026), 104986] - Pengfei Zhang; Huihuang Luo; Ke Zhang; Xiaoyu Cui; Yuling Huang; Shunxin Feng; Jiefan Niu (Journal of Contaminant Hydrology, 2026)

Exploring nonlinear responses of hydrodynamics and algal biomass to restoration measures in a eutrophic shallow urban lake - Pengfei Zhang; Huihuang Luo; Ke Zhang; Xiaoyu Cui; Yuling Huang; Shunxin Feng; Jiefan Niu (Journal of Contaminant Hydrology, 2026)

The plant ontology of cell types - Hongyu Chen; Pu Liang; Xiaolin Lu; Shuai Jiang; Jingjing Jin; Jiaqi Cai; Yaqian Lu; Dihuai Zheng; Jie Yao; Qinjie Chu; Huixia Shou; Chengxin Fu; et al. (Molecular Plant, 2026)

Biochar and moisture variability shape soil carbon pools via microbial carbon-degrading genes - Yue Pan; Tingting Tan; Jie Meng; Hongpeng Guo; Yingbo Dong; Yukui Cui; Na Yu; Xinxin Jin; Yuling Zhang; Hongtao Zou; Nanthi Bolan; Kadambot H.M. Siddique (Journal of Environmental Management, 2026)

Simulation of the impact of the carbon peak target allocation method on the energy structure of electricity generation—based on electricity market equilibrium modeling - Qing Xu; Jue Cui; Feng Dong; Yuling Pan (Clean Technologies and Environmental Policy, 2026)

Genome-wide identification and analysis of paclobutrazol-resistance gene family in cotton and the positive role of GhPRE3 in salt stress and drought stress resistance - Shuaikang Geng; Jingjing Zhai; Bingkai Cui; Huiyun Shan; Zili Liu; Jiahui Li; Cong Wang; Yuling Liu; Pengtao Li; Quanwei Lu; Zihan Xiao; Xiaoping Pan; et al. (Functional & Integrative Genomics, 2025)
Compared with other transcription factors, much less studies have been performed on paclobutrazol-resistance (PRE), a subgroup of the extensive bHLH transcription factor gene family, and the research in cotton was also limited. By utilizing the PRE genes and their conserved domains identified in Arabidopsis, a total of 23, 22, 11, and 12 PRE genes were identified from two major cultivated cotton species and their two ancestors, respectively. The cotton PRE gene family was categorized into three subgroups based on evolutionary tree analysis. Motif and intron analyses indicated that the PRE gene has remained highly conserved throughout evolution. Collinearity analysis indicated that gene duplication, particularly through fragment replication, has significantly contributed to the expansion of the cotton PRE family. An exploration of the conserved elements within the PRE gene family uncovered numerous elements associated with plant stress resistance. Additionally, cotton transcriptome and qRT-PCR analysis showed that PRE genes were associated with a variety of abiotic stresses, including salt, drought, and cold treatments. Subcellular localization experiments indicated that the GhPRE3 gene is associated with membrane proteins. Finally, we selected the GhPRE3 gene for a VIGS experiment, which revealed that under salt stress and drought stress conditions, the wilting of leaves in the GhPRE3- silenced plants was significantly more severe than that observed in the control group, with T-AOC levels notably lower and MDA levels significantly higher. Overexpression of GhPRE3 enhanced seed germination and root development in transgenic Arabidopsis thaliana under salt stress and drought stresses. This suggests that GhPRE3 plays a positive regulatory role in cotton tolerance to salt and drought stressed, providing a reference for molecular genetic breeding of cotton with salt and drought tolerance.

Genome-wide identification and functional analysis of TCX gene family and the critical role of GhTCX17 in response to drought and salt stress in cotton - Yangyang Wei; Jingjing Zhai; Shuaikang Geng; Shaoliang Zhang; Yongqing Zhao; Bingkai Cui; Huiyun Shan; Yanhua Li; Cong Wang; Pengtao Li; Yuling Liu; Quanwei Lu; et al. (Functional & Integrative Genomics, 2025)

Retraction notice to “A comparative study on rapid qualitative and quantitative determination of olive oil adulteration” [Food Chem. 465 (2025) 142126] - Lijuan Du; Ying Yu; Yuling Cui; Guangbin Cui (Food Chemistry, 2025)

Environmental impacts and carbon reduction benefits of mining photovoltaic systems: A case study of Ningdong coal base - Yongliang Zhang; Peixian Li; Ximin Cui; Guorui Wang; Yuling Zhao; Guangyao Zhu (Journal of Cleaner Production, 2025)

Evaluation of Heavy Metals and Essential Minerals in the Hair of Children with Autism Spectrum Disorder and Their Association with Symptom Severity - Xulan Zhou; Xiaochun Xia; Liming Li; Yaohui Ye; Qihui Chen; Mingyue Ke; Qian Cui; Yuling He; Yiting Chen; Shaoqing Lin; Wenlong Liu; Juan Wang (Biological Trace Element Research, 2025)

China's non-energy-intensive sectors have greater carbon reduction potential: Based on a three-tier SDA approach from energy substitution perspective - Chang Qin; Feng Dong; Yangfan Li; Xiaoyun Zhang; Yuling Pan; Caixia Li; Jue Cui (Environmental Impact Assessment Review, 2025)

Endogenous stem cell repair strategy via electromechanical interaction for stress injury - Honglin Xiang; Fan Wang; Qing Zhang; Zeyu Han; Yefei Lei; Neng Lai; Ke Jiang; Hanfeng Yang; Wenguo Cui; Yuling Li (Chemical Engineering Journal, 2025)

RETRACTED: A comparative study on rapid qualitative and quantitative determination of olive oil adulteration - Lijuan Du; Ying Yu; Yuling Cui; Guangbin Cui (Food Chemistry, 2025)

Biochar supporting and sulfidation synergistically affect reactivity of nanoscale zerovalent iron towards sulfamethoxazole - Mi Li; Tiao Zhang; Jing Wang; Xiaoyu Xiao; Xinyi Zeng; Cui Hu; Xiaoming Zou; Wei Hui; Yuling Zheng (Chemical Engineering Journal, 2025)

Nuclear factor NF-YA4a regulates salt stress tolerance and juvenile-adult phase transition in Pyrus - Yingjie Yang; Yuling Mei; Xueping Li; Ran Wang; Chunhui Ma; Jiankun Song; Zhenhua Cui; Jianlong Liu; Xiaozhi Zhou; Dingli Li (Horticulture, Environment, and Biotechnology, 2025)

Evaluation of the efficacy of disinfectants and disinfection methods against Ascaris suum eggs - Ruisi Zhang; Maolin Lu; Hongyan Yu; Tianlu Liu; Zhiying Cui; Yuling Yang; Mengchao Zhou; Yaxian Lu; Hang Tian; Lihong Tian; Lei Han; Zhijun Hou (Veterinary Parasitology, 2024)

A multi-perspective assessment of satellite surface Ozone products in China: Spatiotemporal variability, land cover impacts and pollution monitoring capability - Jian Wang; Yuling Du; Tianxiang Cui; Jibo Yue; Lin Sun; Haiping Si; Ping Dong; Hebing Liu; Yong Li; Lei Shi (Remote Sensing Applications: Society and Environment, 2024)

Highly efficient degradation of ethanol, acetaldehyde, and ethyl acetate removal by bio-trickling filter reactors with various fillers - Hairong Jiang; Yue Wang; Yuling Zhang; Yixuan Yang; Ruoqi Cui; Lianhai Ren; Minglu Zhang; Yongjing Wang (Process Safety and Environmental Protection, 2024)

Monitoring nonlinear large gradient subsidence in mining areas through SBAS-InSAR with PUNet and Weibull model fusion - Yuanjian Wang; Ximin Cui; Chunqing Ge; Yuhang Che; Yuling Zhao; Peixian Li; Yue Jiang; Xiaoqing Han (Environmental Science and Pollution Research, 2024)

Intelligent Detection of 3D Anchor Position Based on Monte Carlo Algorithm - Zekai Cui; Xueli Zhang; Yuling Chen; Liang Cao; Zeguo Zhang; Zuchao Liang; Meijie Zhou; Jiawen Li; Xiaowen Li (Journal of Marine Science and Engineering, 2024)
With the increase in port throughput and the development of the trend of large-scale ships, selecting applicable anchor positions for ships and ensuring the rational and comprehensive utilization of anchorage areas have become a key issue in utilizing the rate of anchorage resources, ensuring the safety of ships anchoring operations and promoting the development of the shipping industry. Existing anchor position selection and detection algorithm studies are limited to a two-dimensional plane for ship anchor position selection, with few studies considering intelligent detection algorithms for safe ship anchoring water depths based on three-dimensional space, considering conditions such as wind and waves. By considering water depth conditions and the objectives of anchorage safety issues, this study proposes an intelligent detection method for ship anchor detection to find the ship’s ideal anchor location in the anchorages by applying the Monte Carlo algorithm. In the processing step, in combination with the Monte Carlo random plane anchor position detection algorithm and Monte Carlo random sampling water depth detection method, the anchor position circle radius model, safe spacing model, anchoring area detection model and safe water depth model are used for examining the anchorage area for awaiting the ship in three-dimensions. To verify the accuracy of the proposed model, based on the scale of common ship types and considering the most conservative parameters, a series of simulation experiments are conducted to check whether the water depth meets the requirements and fully ensure the safety of the experimental results. The research results indicate that the detection almost cover the whole anchorage area and obtain safe water depth restrictions. This method helps to improve the efficiency of ship anchoring and makes actual anchoring operations safer. Under the premise of ensuring sufficient safe spacing between ships, the anchorage ground can accommodate more ships and simulate multi-type ship anchor position detection operations concerning various ship-type parameters to further ensure the safety of ship anchoring.

Early-relief effects of tetrahedral DNA nanostructures-assisted depression therapy via modulates hippocampal neurogenesis and neuroplasticity - Yikai Dou; Xiao Yang; Yue Du; Weitong Cui; Yuling Luo; Jinxue Wei; Liansheng Zhao; Xiaoxiao Cai; Xiaohong Ma; Yunfeng Lin (Chemical Engineering Journal, 2024)

Quantitative in situ Raman spectroscopy investigation on HSO4− dissociation at high pressures (up to 420 MPa) and its geological implication - Hao Cui; Zimeng Li; Richen Zhong; Joël Brugger; Yuling Xie; Chang Yu; Huan Chen; Yifan Ling (Geochimica et Cosmochimica Acta, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

Plowing drag-adaptive operation control method based on motor temperature compensation for electric tractor - Qi Wang; Xudong Wang; Wei Wang; Yongjie Cui; Yuling Song (Journal of Terramechanics, 2024)

A multi-layer nanocased model to explain the U-shaped evolution of shale gas permeability at constant confining pressure - Wangxing Cheng; Guanglei Cui; Yuling Tan; Derek Elsworth; Chunguang Wang; Chengxiang Yang; Tianyu Chen; Chuanzhong Jiang (Fuel, 2024)

Eocene lacustrine microbialites in the western Qaidam Basin, China: implication for the sedimentary record and hydrocarbon potential - Xiang Li; Jiangong Wang; Guohui Long; Li Xu; Jun Cui; Xiujian Sun; Yuling Wang (Carbonates and Evaporites, 2024)

Joint control method based on speed and slip rate switching in plowing operation of wheeled electric tractor equipped with sliding battery pack - Qi Wang; Xudong Wang; Wei Wang; Yuling Song; Yongjie Cui (Computers and Electronics in Agriculture, 2023)

Real-time missing seedling counting in paddy fields based on lightweight network and tracking-by-detection algorithm - Jinrong Cui; Hong Zheng; Zhiwei Zeng; Yuling Yang; Ruijun Ma; Yuyuan Tian; Jianwei Tan; Xiao Feng; Long Qi (Computers and Electronics in Agriculture, 2023)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

GRK5 Deficiency in the Hippocampus Leads to Cognitive Impairment via Abnormal Microglial Alterations - Hongtao Shen; Tianzhen Zhang; Yao Ji; Yu Zhang; Yongxiang Wang; Yuling Jiang; Xiongjin Chen; Qiuhao Liang; Kefeng Wu; Yunfeng Li; Xingyu Lu; Lili Cui; et al. (Molecular Neurobiology, 2023)

Atmospheric particulate matter impairs cognition by modulating synaptic function via the nose-to-brain route - Chunmei Liang; Yuling Jiang; Tianzhen Zhang; Yao Ji; Yu Zhang; Yuanhong Sun; Shengnan Li; Yi Qi; Yan Wang; Yujie Cai; Tianwen Lai; Lili Cui (Science of The Total Environment, 2023)

The reaction mechanism of highly dispersed Cu atoms and ultrafine MnOx nanoclusters co-modified ZSM-5 based on in-situ heteronuclear substitution for catalytic oxidation C6H14 - Jian Li; Jingnan Hu; Yingjie Shi; Jiajia Zhao; Hongchang Wang; Shuang Deng; Yutao Cui; Fan Wang; Hongyan Long; Yuling Tan (Chemical Engineering Journal, 2023)

A new challenge in melon resistance breeding: the ToLCNDV case - Lampros Siskos; Lei Cui; Chen Wang; Richard G. F. Visser; Yuling Bai; Henk J. Schouten (Euphytica, 2022)
Tomato leaf curl New Dehli virus (ToLCNDV) is a whitefly transmitted plant virus that is affecting European melon cultivation for over a decade. Since its first introduction in the Mediterranean basin the virus has been associated with significant economic losses including lower yields and cracked non-marketable fruits in Spain and other key cucurbits production areas. Since there is no chemical application against viral pathogens the focus is geared towards resistance breeding. Various QTLs associated with ToLCNDV resistance have been reported over the recent years in melon and other cucurbits. In the current review we summarize the latest advances in melon breeding for ToLCNDV resistance and present all relevant loci known so far in cucurbits. As a way forward in the future we propose an alternative to traditional resistance gene introgression breeding by exploiting the knowledge on genes that confer susceptibility to the virus in melon and other cucurbits.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

Induction of apoptosis in HepG2 cells by polysaccharide MEP-II from the fermentation broth of Morchella esculenta - Meili Hu; Yan Chen; Cui Wang; Huali Cui; Peilu Duan; Tianlong Zhai; Yuling Yang; Shaofei Li (Biotechnology Letters, 2013)

Molecular cloning, sequence and expression analysis of ZmArf2, a maize ADP-ribosylation factor - Yanyang Liu; Junzhou Li; Yuling Li; Mengguan Wei; Qingxin Cui; Qilei Wang (Molecular Biology Reports, 2010)